Behaviour of precast concrete joints subject to a missing column scenerio - Tan, Wilson Yongli. (2012)
The trend to streamline construction efficiency and buildability has substantially increased the employment of precast concrete products on an international level. Private practitioners recognize that speedy and high quality manufacturing of structural components prior to erection will certainly reduce the high variable labor and time costs required for conventional building methods.